The potential of audiomagnetotellurics in the study of geothermal fields: A case study from the northern segment of the La Candelaria Range, northwestern Argentina - Barcelona, Hernan (2013)
Despite its reduced penetration depth, audiomagnetotelluric (AMT) studies can be used to determine a broad range of features related to little studied geothermal fields. This technique requires a stepwise interpretation of results taking into consideration diverse information (e.g. topographic, hydrological, geological and/or structural data) to constrain the characteristics of the study area. In this work, an AMT study was performed at the hot springs in the northern segment of the La Candelaria Range in order to characterize the area at depth. Geometric aspects of the shallow subsurface were determined based on the dimensional and distortion analysis of the impedance tensors. Also, the correlation between structural features and regional strikes allowed us to define two geoelectric domains, useful to determine the controls on fluid circulation. The subsurface resistivity distribution was determined through 1D and 2D models. The patterns of the 1D models were compared with the morpho-structure of the range. Shallow and deep conductive zones were defined and a possible shallow geothermal system scheme proposed. A strong correlation was found between the AMT results and the geological framework of the region, showing the relevance of using AMT in geothermal areas during the early stages of subsurface prospecting.